CRITICAL SUCCESS FACTORS FOR AFFORDABLE HOUSING: EVIDENCE FROM LOWER-MIDDLE INCOME AND HIGH-INCOME ECONOMIES - Shah, Mona N; Mulliner, Emma; Singh, T. P.; Ahuja, Arun K. (Journal of Surveying, Construction and Property, 2022)
The provision of affordable housing is a pressing challenge that exists around the globe. Successful completion of affordable housing projects is, therefore, of great significance in both developed and developing countries. The primary objective of this paper is to identify the Critical Success Factors (CSFs) for affordable housing projects. To achieve this a comprehensive review of international literature is conducted to identify relevant factors. Nine groups of CSFs were formed, namely: Policy and government support; Land and planning process; Role of Financial Institutions and funding aspects; Sustainability; Designing and materials selection; Approvals, procedures, and clearances; Project management and value engineering; Infrastructure development of Project; and Facility Management. Subsequently, a survey is conducted with experts in India in order to validate and rank the criticality of the identified success factors in the Indian context. Expert rankings are provided for a range of affordable housing products. The results indicate that ‘policy and government support’, ‘land and planning process’, ‘role of financial institutions and funding aspects’ and ‘approvals, procedures and clearances’ are generally the top four CSFs for affordable housing projects. However, the results also indicate that importance of the CSFs was found to vary across different housing products (social, public, and private housing and rental and ownership models). A secondary objective of this paper is to identify differences in approaches to the implementation of the established CSFs in practice. The paper presents a case study comparison between India (a lower-middle income country) and the UK (a high income developed country). Pune in India and London in the UK are compared to determine how well countries of different income levels are achieving the established CSFs. Results suggests a variation in the local contexts in the delivery of successful affordable housing and it is found that developed countries are better at government support and policies, land planning, and incentives to developers for affordable housing delivery.